The association of different types of human milk with bronchopulmonary dysplasia in preterm infants - Pütz, Elisabeth; Ascherl, Rudolf; Wendt, Thomas; Thome, Ulrich H.; Gebauer, Corinna; Genuneit, Jon; Siziba, Linda P. (Frontiers in Nutrition, 2024)
Objective: To evaluate the association between different types of human milk feeds and bronchopulmonary dysplasia (BPD) in preterm infants. Methods: Data on dispensed mother’s own milk (MOM) and donor human milk (DHM) from Leipzig Milk Bank for hospitalized infants with a gestational age (GA) ≤32 weeks observed from birth to 36 weeks’ postmenstrual age or prior discharge were used. BPD was assessed based on documented ICD diagnosis and on electronic hospital records (EHR) of data on ventilation and oxygen supplementation. Associations of dispensed milk feed variations with BPD were investigated using logistic regressions in crude and adjusted models. Results: 866 infants were included with a BPD prevalence of 15.4% (EHR) and 23.2% (ICD). The mean GA was 29.1 weeks. The majority (84.4%, n=746) of infants were nurtured with a mix of MOM, DHM supplemented by formula or parenteral (other) nutrition during hospitalization. For which, MOM comprised the highest median [Q1-Q3] percentage proportion (53[31–81] %) of this mix. Exclusive fresh milk and exclusive MOM feeds were dispensed on a mean of 40% and 34% patient-days, respectively. Statistically significant associations with lower BPD incidence were only observed for 70%-80% MOM vs DHM, and 60% fresh vs frozen milk, in crude and adjusted models. Conclusion: Our findings suggest a protective association of MOM and fresh milk with lower odds of BPD, which may be dependent on the proportion of MOM or fresh milk administered. These results highlight the importance of MOM as an ideal source of nutrition during early infancy.